2014
DOI: 10.1186/1471-2458-14-832
|View full text |Cite
|
Sign up to set email alerts
|

Newcomers in a hazardous environment: a qualitative inquiry into sex worker vulnerability to HIV in Bali, Indonesia

Abstract: BackgroundWomen new to sex work and those with a greater degree of mobility have higher risk of HIV infection. Using social capital as a theoretical framework, we argue that better understanding of the interactions of micro-level structural factors can be valuable in reshaping and restructuring health promotion programmes in Bali to be more responsive to the concerns and needs of newcomer and mobile female sex workers (FSWs).MethodsWe conducted interviews with 11 newcomer FSWs (worked < six months), 9 mobile F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(57 citation statements)
references
References 38 publications
3
52
0
2
Order By: Relevance
“…To reach all YWSS, programmes should consider network‐based approaches and use of incentivized referral vouchers, with feasibility of this approach among non‐identifying ‐YWSS demonstrated by this study. Trained peer educators should also be engaged, as they may reach younger FSW , and may prove important to retain YWSS in programmes and develop social capital among non‐identifying‐YWSS, which has been associated with increased condom use .…”
Section: Discussionmentioning
confidence: 99%
“…To reach all YWSS, programmes should consider network‐based approaches and use of incentivized referral vouchers, with feasibility of this approach among non‐identifying ‐YWSS demonstrated by this study. Trained peer educators should also be engaged, as they may reach younger FSW , and may prove important to retain YWSS in programmes and develop social capital among non‐identifying‐YWSS, which has been associated with increased condom use .…”
Section: Discussionmentioning
confidence: 99%
“…We want to note that condom use is not merely an individual choice. Sex work in Indonesia (and in brothels) is illegal, and district police periodically enforce the law by arresting the FSWs or deporting them back to where they come from [17] as most of them are migrants. These conditions create a challenge to provide care and deliver behavioural change interventions to increase condom use through health education programs [18], and a dilemma for health authorities in providing health services and health promotion programs because they do not wish to be seen as supporting or legalising prostitution.…”
Section: Exercising Identity and Condom Usementioning
confidence: 99%
“…In addition to work locations, prior research found that women who were new to sex work lacked knowledge about HIV prevention practices and had weaker beliefs about their ability to enforce these practices during sex work [16]. Older age was another factor associated with higher prevalence of HIV, syphilis infections, unprotected sex, and injection drug use [17, 18].…”
Section: Introductionmentioning
confidence: 99%